Physical Activity Patterns of Latina Immigrants Living in Alabama - Sweatt, Sarah Katherine (J Racial Ethn Health Disparities, 2015)
BACKGROUND: Latinos are the fastest growing minority group in the Southeastern USA. Latinos living in the USA have a higher prevalence of obesity, metabolic diseases, and physical inactivity compared to non-Latino Whites, particularly Latina women. The objective of this study is to assess the patterns of physical activity (PA) in overweight Latina immigrants in Alabama using a self-report and an accelerometer. METHODS: Participants included foreign-born Latina women age ≥19 years with BMI ≥25 kg/m(2). The Global Physical Activity Questionnaire was used to assess self-reported physical activity. Accelerometers were used as an objective measure of physical activity. RESULTS: Among 44 overweight/obese Latina immigrants (mean age 36.6 years and BMI 33.3 kg/m(2)), 36.4 % met PA recommendations by self-report while only 20.5 % met recommendations according to the accelerometer. Self-report sedentary activity was underestimated (186 min/day self-report vs. 575 min/day accelerometer) while moderate activity was overestimated (34 min/day self-report vs. 15 min/day accelerometer). While the number of years living in the USA was positively associated with vigorous activity (r=0.32, p= 0.03), the number of years living in Alabama tended to be positively associated with sedentary activity and negatively associated with moderate activity. CONCLUSIONS: Latina immigrants living in Alabama overestimated the amount of time spent in moderate PA and underestimated time spent in sedentary activity.